An Unintended Effect of Financing the University Education of the Most Brilliant and Poorest Colombian Students: The Case of the Intervention of the Ser Pilo Paga Program - Pablo Medina; Natalia Ariza; Pablo Navas; Fernando Rojas; Gina Parody; Juan Alejandro Valdivia; Roberto Zarama; Juan Felipe Penagos (Complexity)
In this paper, we show an unintended effect of the program Ser Pilo Paga (SPP) that was a flagship program of the Colombian government between 2014 and 2018. It was designed as an intervention in the Colombian Higher Education System (CHES) by awarding, in the steady state, individual funding to about 40,000 students. Every year, 10,000 new students were chosen from the best applicants in the top decile of the population in the entrance exam to higher education in Colombia that also came from families that live under the level of poverty according to a national survey. Our approach, based on an intensive study of the changes in the statistical distributions of the exam scores during these four years, provides evidence of student performance improvements not only of the beneficiaries of the program, but also of the whole student population. This shows that the program opened similar opportunities for all the students, especially for the poorest ones. The program drove a reduction in the gap between students of the upper strata of the population and those of the lowest strata that usually did not access a high quality institution of higher education due to the lack of funding. This result has opened a debate about the optimal way of funding higher education.